Renal angiomyolipoma and lymphangioleiomyomatosis in pregnancy. (August 2013) - Iruloh, C.; Keriakos, R.; Smith, D. J.; Cleveland, T.
Abstract : This is a literature review for management of angiomyolipoma (AML), lymphangioleiomyomatosis (LAM) and tuberous sclerosis (TS) during pregnancy, prompted by a case of a 23-year-old woman who presented with generalised itching at 31 weeks' gestation and was found to have a large vascular retroperitoneal mass in the lower pole of the left kidney. Magnetic resonance imaging (MRI) was suggestive of angiomyolipoma with multiple large aneurysms and haemorrhage within the tumour. She was delivered at 38 weeks by elective caesarean section, to avoid the risk of rupture and bleeding from the aneurysms during labour. Further imaging, with MR angiogram, computed tomography (CT) of the abdomen and pelvis and high resolution CT (HRCT) of the chest, confirmed lymphangioleiomyomatosis with left AML. She had embolisation of the AML performed twice, 8 weeks apart after delivery and subsequently had a left nephrectomy.